2014
DOI: 10.1155/2014/715316
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Hepatic Blood Perfusion by Laser Speckle Imaging and Changes of Hepatic Vasoactive Substances in Mice after Electroacupuncture

Abstract: The study was conducted to observe the effect of electroacupuncture (EA) on hepatic blood perfusion (HBP) and vascular regulation. We investigated 60 male anesthetized mice under the following 3 conditions: without EA stimulation (control group); EA stimulation at Zusanli (ST36 group); EA stimulation at nonacupoint (NA group) during 30 min. The HBP was measured using the laser speckle perfusion imaging (LSPI). The level of nitric oxide (NO), endothelin-1 (ET-1), and noradrenaline (NE) in liver tissue was detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Our experiments revealed that EA significantly reduced the DES-induced overexpression of CGRP, SP, VIP, PACAP, NO and ET-1 in recurrent migraine model rats. Similarly, in some studies, EA reduced the level of SP [68], CGRP [69], VIP [70–72], NPY [73], NO [74] and ET-1 [75] in plasma or some tissues of other diseases model animals, including dorsal root ganglion, liver, synovial, distal colon, spinal cord, hypothalamus, colonic mucosa, and cardiac tissue. However, we did not observe any effects of EA on the plasma concentrations of NPY.…”
Section: Discussionmentioning
confidence: 91%
“…Our experiments revealed that EA significantly reduced the DES-induced overexpression of CGRP, SP, VIP, PACAP, NO and ET-1 in recurrent migraine model rats. Similarly, in some studies, EA reduced the level of SP [68], CGRP [69], VIP [70–72], NPY [73], NO [74] and ET-1 [75] in plasma or some tissues of other diseases model animals, including dorsal root ganglion, liver, synovial, distal colon, spinal cord, hypothalamus, colonic mucosa, and cardiac tissue. However, we did not observe any effects of EA on the plasma concentrations of NPY.…”
Section: Discussionmentioning
confidence: 91%